1993
DOI: 10.1016/0270-9139(93)90183-n
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C virus infection in hemodialysis patients: A longitudinal study comparing the results of RNA and antibody assays

Abstract: We longitudinally studied 51 patients from two hemodialysis centers to determine the prevalence of hepatitis C virus infection in hemodialysis patients. Serum samples were tested for antibody to HCV by first- and second-generation enzyme immunoassays and for hepatitis C virus RNA by nested polymerase chain reaction assay. Antibody to hepatitis C virus was detected in the initial serum samples by first-generation enzyme immunoassay and second-generation enzyme immunoassay in 6 (11.8%) and 11 (21.6%) patients, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 1 publication
4
43
2
Order By: Relevance
“…The majority of HDpatients with HCVhave only a minimal derangement in the ALTlevel (1,6). However, recent histological analysis of the liver tissue indicates that HDpatients with HCVoften have chronic active hepatitis or cirrhosis (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of HDpatients with HCVhave only a minimal derangement in the ALTlevel (1,6). However, recent histological analysis of the liver tissue indicates that HDpatients with HCVoften have chronic active hepatitis or cirrhosis (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous studies have demonstrated that as manyas 10 to 40%of HDpatients are chronically infected by HCV,although HCV prevalence in HDpatients is highly variable among different countries and even amongHDunits in the same area (1)(2)(3). The high prevalence of HCVin HDpatients is believed to be attributed to the transfusion of HCV-contaminated blood products before the availability of reliable HCVscreening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of HCV infection increases from 12% to 37% after five years on HD. 10 In this study it was also identified that HCV positivity was more in longer duration dialyzed patients. Although two-thirds of the patients were on BT but that did not have any significant influence on prevalence of the hepatitis viruses.…”
Section: Discussionmentioning
confidence: 54%
“…non-establishment of a carrier state, low-level undetectable viraemia, and intermittent viraemia. 15,17 The former is more likely in RT patients and the latter two are more likely in a dialysis setting. In our study HCV-RNA was undetectable in 8.3% of the patients with a positive serology.…”
Section: Resultsmentioning
confidence: 99%